Multifunctional natural agarose as an alternative material for high-performance rechargeable lithium-ion batteries. Issue 9 (20th January 2016) - Hwang, Gaeun; Kim, Ju-Myung; Hong, Dongki; Kim, Choon-Ki; Choi, Nam-Soon; Lee, Sang-Young; Park, Soojin
Abstract : Multifunctional agarose acts as an effective binder for Si anodes and LiMn2 O4 cathodes and also serves as a good carbon source to obtain hard carbon. Abstract : Agarose, which is one of the natural polysaccharides that is generally extracted from seaweed, has recently attracted great attention as an environmentally-benign building element for a wide variety of applications. Notably, its disaccharide repeating units bearing ether/hydroxyl groups carry unprecedented performance benefits far beyond those accessible with traditional synthetic polymers. Herein, intrigued by these unusual chemical features of agarose, we explore its potential applicability as an alternative electrode binder and also as a carbon source for high-performance rechargeable lithium-ion batteries. The agarose binder enables silicon (Si) active materials to be tightly adhered to copper foil current collectors, thereby providing significant improvement in the electrochemical performance of the resulting Si anode (specific capacity = 2000 mA h g −1 and capacity retention after 200 cycles = 71%). In addition, agarose can be exploited as a cathode binder. An LiMn2 O4 cathode containing agarose binder shows an excellent cell performance (initial coulombic efficiency of ∼96.2% and capacity retention after 400 cycles of ∼100%). Through the selective carbonization of Si-dispersed agarose, Si/C (hard carbon) composite active materials are successfully synthesized. Eventually, the Si/C composite anode and the LiMn2 O4 cathode mentioned above are assembled to produce a full cell featuring the use of agarose as an alternative green material. Benefiting from the exceptional multifunctionality of agarose, the full cell presents a stable cycling performance (capacity retention after 50 cycles of >87%).